Habit Formation and Persistence in Individual Asset Portfolio Holdings : The Case of Italy - Munoz, Sonia (IMF Working Papers; Working Paper, 2006)
This paper uses six waves of the Bank of Italy Survey of Households Income and Wealth to explore the dynamics of asset portfolio ownership. The household asset portfolio decision is a choice among discrete alternatives, and I model the problem in a multinomial framework. I focus on a particularly important feature of household portfolio behavior: the infrequency of portfolio allocation changes. I find evidence of strong unobserved heterogeneity through time-varying error components, which I interpret as taste persistence in both the risky and safe asset participation decisions. I estimate the model using the method of maximum smoothly simulated likelihood.